Temperature influences growth, digestive system ontogeny and lipids deposition in the liver in gilthead seabream (Sparus aurata) larvae and juveniles - de Mello, Paulo H. [UNESP]; Divanach, Pascal; Papadakis, Ioannis E. (Hindawi, 2022)
The effects of three temperatures (16°C, 19°C and 22°C) during the seabream larval rearing period (60 days) were studied in terms of growth (total length, T.L.), the ontogeny of the digestive system and lipid deposition in the liver (area covered with lipid vacuoles, ACLV%). The trials were performed in duplicate for each treatment. Seabream eggs were stocked (100 eggs L−1) in each 500-L tank. The larvae were reared using an intensive rearing protocol, which offers a combination of enriched rotifers (5 to 7 ind ml−1) followed by Artemia nauplii (0.5 ind ml−1) and finally with dry artificial food, the provision of which started when the total length of larvae was close to 15 mm. The ontogeny of the digestive system and the estimation of ACLV in the liver were performed using histological and image analysis methods. The results showed that the studied parameters were affected by temperature variation. The total length of larvae at the end of the rearing procedure was significantly higher at the temperature groups of 22°C (24.1 ± 3.6 mm) and 19°C (20.11 ± 1.8 mm) than the group of 16°C (12.6 ± 2.1 mm). The rate of digestive system ontogenesis was analogous to the temperature as it was completed (stomach with gastric glands appearance) at 33 dah (T.L. 9.55 ± 0.1.47 mm, 726-degree days), 35 dah (T.L. 11.00 ± 0.78 mm, 665-degree days) and 60 dah (T.L. 12.86 ± 1.68 mm, 960-degree days) in the groups 22°C, 19°C and 16°C respectively. Four distinctive phases were presented concerning the pattern of ACLV in the liver. At the first phase (from 8 to 16 dah), the ACLV was mainly higher in the 16°C and 19°C groups. During the second phase (from 19 to 35 dah), the 16°C group showed higher lipid accumulations. There was a high variation among groups in the third phase (39–45 dah). Finally, in the fourth phase (47–60 dah), the 22°C and 16°C groups showed higher liver lipid accumulation. Compared with the temperatures studied for seabream, the most appropriate rearing temperature is 19°C, constituting a cost-effective method for larval rearing. The effectiveness of the histological liver lipid analysis indicates an accurate method to evaluate feeding conditions during seabream larval rearing, indicating critical feeding periods with precision.
Keywords: digestive tract; fish development; larvae; liver; Seabream